Las reformas tributarias del impuesto a la renta régimen impositivo microempresas y su impacto en la recaudación tributaria de Ecuador - Menéndez García, Janara Melissa (2023)
The objective of the investigative work was to evaluate the impact of the tax reforms of the income tax microenterprise tax regime on the tax collection in Ecuador, to achieve this objective a series of steps were followed, such as carrying out a comparative analysis between the previous tax norm and current income tax of the microenterprise tax regime; determine the tax collection for income tax of the general and microenterprise regime and measure the economic impact caused by the tax reform to the microenterprise regime in the collection of income tax, in the period 2018-2021. The methods used in the investigation were inductive, deductive, analytical, descriptive, synthetic and comparative, and among the techniques used, the bibliographic review.